Análise comparativa da eficiência de mecanismos de consenso Proof-of-Stake com e sem comitês de validação - Dias, Matheus Acauã; Henriques, Marco Aurélio Amaral (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems Security, 2023)
This work aims to analyze and compare the performance of two proof-of-stake consensus mechanisms for public blockchains: Casper (proposed by the Ethereum cryptocurrency group) and Committeeless Proof-of-Stake (CPoS, proposed by the ReGrAS/Unicamp group). The study is based on a theoretical and practical analysis of the two mechanisms, with the aim of identifying the advantages and limitations of each one, in order to offer a deeper understanding of these mecanisms by identifying constraints and enhancements.